OXIDATIVE STRESS RESPONSES IN Oreochromis niloticus (LINNAEUS, 1758) EXPOSED TO AQUEOUS SOLUTIONS OF TWO COMMON POND FERTILIZERS IN CULTURE MEDIA - OKE, Abdulfatai Olubukola (Nigerian Journal of Fisheries, 2025)
A bioassay was conducted to determine oxidative stress responses in Oreochromis niloticus exposed to aqueous solutions of NPK 15-15-15 and layer manure (LM) fertilizers, simulating concentrations resulting from the recommended application rates (RARs) of 120kg/ha/2weeks and 224kg ha/week respectively, on a 1ha pond of 0.8m depth. These RARs were serially diluted to yield 0.0mg/l, 15mg/l of NPK 15-15-15 and 28mg/l LM solutions, designated as control, treatments 1 and 2, respectively. Experimental units were rearing troughs of dimensions 1m×1m×0.5m filled to the 250-litre mark. Post-yolk sac larvae of O. niloticus were raised in the fertilizer solutions for a period of six months at a stocking density of 100 larvae/rearing trough. The levels of reactive oxygen species (ROS), superoxide dismutase (SOD), and total protein (TP) of O. niloticus were determined before exposure (initial samples), at 4, 84 and 168 days of exposure, following standard procedures. Temperature, dissolved oxygen, pH, total water hardness, nitrate and phosphate were monitored. Levels of TP, SOD, and ROS in initial and control were significantly different (p<0.05) from levels in fish challenged with N-P-K 15-15-15, and LM at 4, 84, and 168 days of exposure. TP had significant negative correlations with ROS (-0.985, p<0.0001) and SOD (-0.999, p<0.0001). ROS and SOD had significant correlations (r = 0.988, p<0.0001). All the oxidative stress indices and the physicochemical variables, had high regression coefficients with fertilizer solutions (r=0.724 – 1.000, p<0.0001), except pH and PO4. Since fish are often used as bio-indicators in aquatic toxicity tests, the findings suggest that fertilizer runoffs could be causing widespread damage to inland water ecosystems, potentially impacting their productivity.